2018
DOI: 10.13031/trans.12553
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Functional Properties of Nine Proso Millet Cultivars

Abstract: Right click to open a feedback form in a new tab to let us know how this document benefits you.ABSTRACT. Evaluation of the postharvest properties of nine proso millet cultivars was carried out to determine their physical and engineering properties, which are very useful for designing appropriate systems for process operations such as sorting, drying, heating, cooling, and milling. Nine cultivars of proso millet comprising waxy and non-waxy types, namely Cope, Earlybird, Huntsman, Minco, Plateau, Sunrise, Rise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…GF bread with 100 percent proso millet was significantly ( p <0.05) harder than the other two formulations. Starch has a way of improving the textural characteristics of bread because of the porous structure that is enhanced by starch swelling (Singh, 2016). This can also be correlated with the specific volume as shown in Table IV.…”
Section: Resultsmentioning
confidence: 99%
“…GF bread with 100 percent proso millet was significantly ( p <0.05) harder than the other two formulations. Starch has a way of improving the textural characteristics of bread because of the porous structure that is enhanced by starch swelling (Singh, 2016). This can also be correlated with the specific volume as shown in Table IV.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these values, the calculated values of GMD range from 0.74 mm (Teff millet “Trotter” variety) to 3.36 mm (pearl millet “SOSAT C88” variety) (Gaurav et al, 2021; Zewdu & Solomon, 2007). Based on sphericity, the millets can be grouped as oval shape ranging from 0.6 to 0.7 (pearl millet “Ex‐Borno” variety, little millet, and browntop millet), spheroid shape ranging from 0.7 to 0.8 (pearl millet “SOSAT C88” variety, barnyard millet, foxtail millet, finger millet “Black” variety, and kodo millet), and round shape ranging from 0.8 to 0.9 (proso millet, finger millet “Milky cream” variety, and “Brown” variety) (Gaurav et al, 2021; Nagaraju et al, 2020; Ojediran et al, 2010; Singh et al, 2018). The values for TSW of the different millet grains range from 2.49 g (little millet) to 11.95 g (pearl millet “SOSAT C88” variety).…”
Section: Physical Properties Of Milletsmentioning
confidence: 99%
“…Table 3 shows that the use of WCF led to an increase in the gumminess of the samples, while no significant differences were observed for springiness. Singh et al [44] also determined the effect of combination of corn and potato starch on millet-based breads. These authors found that corn starch rose bread volume and led to a decrease in bread firmness.…”
Section: Comparison Of the Quality Properties Of Gluten-freementioning
confidence: 99%